PENGARUH DERAJAT SANGRAI BIJI KOPI ARABIKA (coffea arabica) DENGAN PENAMBAHAN BUBUK SERAI DAPUR (Cymbopogon citratus) TERHADAP SIFAT KIMIA DAN SENSORI KOPI CELUP - Eva Murlida; Miftahul Hamdi; Yusriana Yusriana (Jurnal Teknologi dan Industri Pertanian Indonesia, 2025)
The coffee brewing that is most often found in the community is manual or brewing coffee. However, this method is considered to still have weaknesses and is less practical because it leaves coffee grounds in the drink. One effort to overcome this problem is coffee in pouch packaging, and the addition of spices to diversify products. This research aims to study the effect of the degree of roasting of Arabica coffee beans and the percentage of added lemongrass powder on the chemical and sensory properties of coffee bag products. This research used a factorial completely randomized design (RAL). Experimental factors used in this study are the degree of roasting of Arabica coffee beans (D) which consists of 3 levels including 1900C (light) (D1), 2100C (medium) (D2) and 2400C (dark)(D3). The second factor is the concentration of kitchen lemongrass powder (S) which consists of 2 levels, namely 8% (S1) and 10% (S2). The research data obtained is then analyzed using Analysis of Variance (ANOVA) and followed with Duncan's Multiple Range Test (DMRT) if there are differences between treatments. The results of various types of roasting degree treatments had an effect on reducing water content, ash content, and total dissolved solids. The value of water content and ash content decreases as the degree of roasting increases, the value of total dissolved solids increases as the degree of roasting increases. The percentage of adding kitchen lemongrass powder also has an effect on reducing the ash content. The ash content value increased as the percentage of lemongrass powder was added. The interaction between the degree of roasting and the addition of lemongrass powder affects pH and hedonics (aroma, color and taste). The pH value increases as the degree of roasting increases and the addition of lemongrass powder. The average value of the aroma hedonic test was 3.55 (neutral), color hedonic 3.62 (liked) and taste hedonic 3.35 (neutral). The best treatment was obtained at a light roast level with an additional percentage of 8% kitchen lemongrass powder (D1S1) followed by antioxidant activity testing with a result of 52%.